The effects of tax and promotion on rubber medical devices export - Lee, Siu Ming; Radziah Adam; Ku’ Azam Tuan Lonik (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the effects of cess and export promotion on rubber medical devices export by employing a modified gravity model. The export promotion activities include overseas office, trade missions and trade fairs. Using a balanced panel data of Malaysia, the findings show that cess reduces rubber medical devices export indicating its potential of limiting this export. The results further show that overseas office establishment increases rubber medical devices export growth. These two sets of policies, namely cess and export promotion activities are indeed intertwined and are difficult to be considered separately. In increasing global market share for rubber medical devices, Malaysia continues its export promotion efforts and cess is currently the sole funding.